2021
DOI: 10.3389/fpsyg.2021.684248
|View full text |Cite
|
Sign up to set email alerts
|

Predicting One’s Turn With Both Body and Mind: Anticipatory Speech Postures During Dyadic Conversation

Abstract: In natural conversation, turns are handed off quickly, with the mean downtime commonly ranging from 7 to 423 ms. To achieve this, speakers plan their upcoming speech as their partner’s turn unfolds, holding the audible utterance in abeyance until socially appropriate. The role played by prediction is debated, with some researchers claiming that speakers predict upcoming speech opportunities, and others claiming that speakers wait for detection of turn-final cues. The dynamics of articulatory triggering may spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 52 publications
(70 reference statements)
1
9
1
Order By: Relevance
“…Comparing the present results to those from [ 35 ], on articulatory preparation (in the form of lip openings) in spontaneous conversation, one can say that the overall conclusions of the two studies appear compatible with each other. In a video corpus of spontaneous conversation, these authors compared how far participants opened their lips in advance of turns starting with sounds that required large versus small lip openings.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Comparing the present results to those from [ 35 ], on articulatory preparation (in the form of lip openings) in spontaneous conversation, one can say that the overall conclusions of the two studies appear compatible with each other. In a video corpus of spontaneous conversation, these authors compared how far participants opened their lips in advance of turns starting with sounds that required large versus small lip openings.…”
Section: Discussionsupporting
confidence: 86%
“…Although the used measure was quite different from that used in the present study, both opening the lips and moving the tongue are actions that are likely to be performed in order to prepare for articulation of certain speech sounds or phonemes. The study [ 35 ] found that articulatory preparation could start several seconds before a response, especially for short responses. These effects even were present even longer before the response than in the present study, as early as three seconds before (compared to up to two seconds in the present study).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations